Calcium channel β3 subunit regulates ATP-dependent migration of dendritic cells - Woo, Marcel Seungsu; Ufer, Friederike; Sonner, Jana K.; Belkacemi, Anouar; Tintelnot, Joseph; Sáez, Pablo J.; Krieg, Paula F.; Mayer, Christina; Binkle-Ladisch, Lars; Engler, Jan Broder; Bauer, Simone; Kursawe, Nina; et al. (Science advances, 2023)
Migratory dendritic cells (migDCs) continuously patrol tissues and are activated by injury and inflammation. Extracellular adenosine triphosphate (ATP) is released by damaged cells or actively secreted during inflammation and increases migDC motility. However, the underlying molecular mechanisms by which ATP accelerates migDC migration is not understood. Here, we show that migDCs can be distinguished from other DC subsets and immune cells by their expression of the voltage-gated calcium channel subunit β3 (Cavβ3; CACNB3), which exclusively facilitates ATP-dependent migration in vitro and during tissue damage in vivo. By contrast, CACNB3 does not regulate lipopolysaccharide-dependent migration. Mechanistically, CACNB3 regulates ATP-dependent inositol 1,4,5-trisphophate receptor-controlled calcium release from the endoplasmic reticulum. This, in turn, is required for ATP-mediated suppression of adhesion molecules, their detachment, and initiation of migDC migration. Thus, Cacnb3-deficient migDCs have an impaired migration after ATP exposure. In summary, we identified CACNB3 as a master regulator of ATP-dependent migDC migration that controls tissue-specific immunological responses during injury and inflammation.